Müther's shell structures in Germany – a solution to avoid demolition. Issue 3 (8th September 2020) - Riegelmann, Philipp; Schumann, Alexander; May, Sebastian; Bochmann, Jakob; Garibaldi, Maria Patricia; Curbach, Manfred
Abstract : This article is intended to give an overview of an almost forgotten construction form – a great innovation not only in the former German Democratic Republic (GDR) but for the whole world. This type of construction, made of reinforced-concrete shell structures, was brought to perfection, inter alia, by the outstanding civil engineer Ulrich Müther, who was one of the most important engineers in Germany. These structures stand out due to their appearance and their very slim design with large spans. The material shortage in the GDR catalysed the pioneering spirit of Ulrich Müther and resulted in the possibility of building those slender structures. This article should give an overview of the life and work of Ulrich Müther, highlighting his most important shell constructions. Furthermore, the current condition state and the possibilities for preserving these architectural artworks will be discussed. By taking the example of the Hyparshell in Magdeburg, it is shown that the use of the innovative and high-performance building material carbon-reinforced concrete as a strengthening or rehabilitation system allows to keep the slim and filigree nature of the concrete structures and prevent them from being demolished.